(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2024)
The essay examines the importance of the genetic apparatus in the commentary; in this direction, the essay focuses on cases of intertextuality as a laboratory subject to approximations, shot corrections, internal adjustments involving single textual places or, on a macroscopic scale, the overall architecture of the text. Two case studies were examined: Delio Tessa and Vittorio Sereni.